Comparison of Different Microscopic Methods with Conventional TB Culture - Rahman, Farjana; Munshi, Saurab Kishore; Kamal, SM Mostofa; Rahman, ASM Matiur; Rahman, M Majibur; Noor, Rashed (Stamford Journal of Microbiology, 2011)
Tuberculosis is considered as the greatest cause of death worldwide. In the developing countries including Bangladesh, population density, poverty, malnutrition, and highly congested environment may create substantial risk for infection with Mycobacterium tuberculosis. The principal obstacle in the treatment of tuberculosis is the consumption of time and inaccurate diagnosis as well. Therefore, a retrospective study was carried out in order to compare results obtained by both the conventional AFB (Acid Fast Bacilli) microscopy and Lowenstein-Jensen (L-J) culture method for detection of Mycobacterium spp. in clinical samples from different categories of patients. Among one hundred and fifty samples, 83 (55.3%) AFB+ results were found under Bright-Field (BF) microscopy, 78 (52%) AFB+ and 91 (60.7%) AFB+ results were observed under conventional and Light Emitting Diode (LED) fluorescence microscopy. On L-J culture media, 103 (68.7%) AFB+ isolates were found which reveals that the culture could be a gold standard for diagnosis of TB. Significantly, the sensitivity and specificity of LED fluorescence microscopy was higher than those of other microscopic methods compared to culture. The resistance rate of isolates was higher for isoniazid (65%) and rifampicin (63.1%) than streptomycin (53.4%) and ethambutanol (38.8%). The isolates showed resistance to more than one drug. Among one hundred and three cases, total 36 (24.7%) cases reported as MDR-TB (resistant to all first-line drugs) in previously treated patients but it was nil in the new cases. Thus, this study emphasizes the need of Directly Observed Treatment Short Course (DOTS) program for selection of proper anti-tubercular drug therapy towards the patient rather than providing them with empirical therapy and thereby reducing the alarming increase of drug resistance. DOI: http://dx.doi.org/10.3329/sjm.v1i1.9133 Stamford Journal of Microbiology, Vol.1(1), July 2011, p.46-50